PENGARUH SOSIALISASI PAJAK, PELAKSANAAN SANKSI DENDA, DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK DALAM MELAPORKAN SPT TAHUNAN PPH ORANG PRIBADI - Solehudin, Mohammad (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2018)
The aims of this research is to determine how socializing influence of tax, penalties andimplementation of service tax authorities on tax compliance in the annual report PPh such as aprivate person either partially or simultaneously or jointly on individual taxpayers who havebusiness or work freely in the district KPP Pratama Kebon Jeruk Satu. This research uses samplerandom sampling and for the types of data uses primary and secondary data types. The primary datasource is obtained directly from the individual taxpayer who has a business or performs listed have aNPWP in KPP Pratama Kebon Jeruk Satu. While secondary data such as the number of individualtaxpayers who registered have income from business or work freely. Independent variables used aretax dissemination, implementation of financial penalities, and service tax authorities. The dependentvariable in this research is the taxpayers compliance. Testing in this research using SPSS 21.0. Theresults of the research showed that the socialization of tax, penalties implementation, and service taxauthorities partially significant effect on tax compliance and simultaneously have a significantimpact also on tax compliance. Implementation of penalties is the most dominant variable or aneffect on tax compliance in reporting SPT Personal Income Tax.